Answer: the answer is c
Step-by-step explanation:
Answer:
I think the answer would just be 2, I'm not for sure on this one
Answer:
(x-3)(x^2-7) = x^3 -3x^2 -7x + 21
just change the sign of the root and put x in front of it, then multiply the factors all together
(x-3)(x-sqr7)(x+sqr7) roots come in conjugate pairs to eliminate irrational coefficients
(x-sqr7)(x+sqr7) = x^2-7. similar to (a-b)(a+b) = a^2-b^2
Step-by-step explanation:
Answer:
x= 5√7
Step-by-step explanation:
Use the Pythagorean theorem
16^2= 9^2 + x^2
x^2=175
x= √175
x= 5√7
I believe that would be 1